Healthy Lifestyle Management System - Abu Bakar, Muhammad Syazwan (Universiti Teknologi Petronas, 2011)
This project focuses on developing the intelligent algorithms to calculate and determines the duration of exercise, time to do exercise and the types of the exercise needed by a user daily. The factors that will affect the calculation of the algorithm are the current BMI (Body Mass Index) of the user; user needs to enter the weight and height to calculate the BMI, the user's body condition and the working hours of the user. System will store all the data inside the database. The main objective of this system is to develop the intelligent algorithm to calculate the exercise needed by the user based on certain criteria. The intelligent algorithm that used in this application is Rule-Based algorithm. This project will help university student manage their time to do exercise just by using the android application inside their phone. The methodology use to develop this project is RAD. This project will produce many versions of prototypes before the actual system. Intelligent Exercise Assistance was developed as the beta version of this project. In overall, this intelligent application will help the student to manage their time, life in healthy lifestyle and maintain their healthy body.